2018
DOI: 10.1016/j.jaac.2018.07.882
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Is an Environmental Predictor of Callous-Unemotional Traits and Aggression: A Monozygotic Twin Differences Study

Abstract: Objective: Callous-unemotional (CU) traits increase risk for children developing severe childhood aggression and Conduct Disorder. CU traits are typically described as highly heritable and debate continues about whether the parenting environment matters in their etiology. Strong genetically-informed designs are needed to test for the presence of environmental links between parenting practices and CU traits. Our objective was to determine whether parental harshness and parental warmth were related to children’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
78
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 63 publications
13
78
2
1
Order By: Relevance
“…Although less than for positive parenting, there is some evidence that negative parenting in young children is associated with the development of CU traits. As previously described (Waller et al, 2018) harsh parenting was associated with both aggression and CU traits in 6-10-year-old children.…”
Section: Negative Parenting As a Risk Factor For The Development Of Csupporting
confidence: 69%
See 2 more Smart Citations
“…Although less than for positive parenting, there is some evidence that negative parenting in young children is associated with the development of CU traits. As previously described (Waller et al, 2018) harsh parenting was associated with both aggression and CU traits in 6-10-year-old children.…”
Section: Negative Parenting As a Risk Factor For The Development Of Csupporting
confidence: 69%
“…Numerous studies have reported similar associations between low positive parenting and CD/HCU or CU traits (e.g., Pasalich et al, 2011;Ray et al, 2017;Elizur & Somech, 2018;Hyde et al, 2016;Pardini et al, 2007;Muratori et al, 2016;Waller et al, 2016;Waller et al, 2017a;Waller et al, 2017b;Waller et al, 2018;but c.f. Falk & Lee, 2012).…”
Section: Group-level Differences In Positive Parentingmentioning
confidence: 89%
See 1 more Smart Citation
“…Both traits are normally distributed in the general population (Chamorro et al, 2012;Georgiev et al, 2013), and the extreme ends of their spectra are marked as maladaptive and pathological (McLennan, 2016). Both genes (Brikell et al, 2018;Moore et al, 2019) and the environment (Gescher et al, 2018;Waller et al, 2018) play important roles in the etiology of impulsive and callous traits.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to bullying perpetration, less is known about the specific underlying heritable characteristics, but such could include, for example, callous-unemotional traits and/or conduct problems (Viding, Simmonds, Petrides, & Frederickson, 2009;. It is important to identify at-risk children early, and intervene not only in the school context but also by means of parenting programs (Waller, Hyde, Klump, & Burt, 2018). Further research is needed to identify specific heritable characteristics related to both the risk of victimization and bullying, especially victimization and bullying that persists after intervention efforts.…”
Section: Discussionmentioning
confidence: 99%